Rapunzel's revenge - Hale, Shannon; Hale, Dean, 1972-; Hale, Nathan, 1976- (New York : Bloomsbury, 2008)
Rapunzel, having grown up in a lovely castle with the woman she thought was her mother, is placed in a very tall hollow tree as punishment after her curiosity prompts her to climb the castle wall and look at the ruin of the world beyond her home, but she is able to escape and, with the help of Jack, embarks on a plan to free the land from the grip of the witch.
Wilson's Children, October 2010.
Wilson's Junior High School, January 2010.
School Library Journal starred, September 2008.
Notable/Best Books (A.L.A.), January 2009.
Horn Book Starred, November 2008.
Library Media Connection starred, November 2008.
Keywords: Revenge -- Comic books, strips, etc -- Juvenile fiction; Outlaws -- Comic books, strips, etc -- Juvenile fiction; Witches -- Comic books, strips, etc -- Juvenile fiction; Characters and characteristics in literature -- Comic books, strips, etc -- Juvenile fiction; Revenge -- Fiction; Hair -- Fiction; Robbers and outlaws -- Fiction; Witches -- Fiction; Characters in literature -- Fiction; Fantasy; Cartoons and comics; Revenge -- Comic books, strips, etc -- Fiction; Criminals -- Comic books, strips, etc -- Fiction; Characters and characteristics in literature -- Comic books, strips, etc -- Fiction; Fantasy comic books, strips, etc; Graphic novels